DIAGNOSA DEPRESI PADA MAHASISWA MENGGUNAKAN METODE CERTAINTY FACTOR DAN FORWARD CHAINING (INTI Nusa Mandiri, 2020)
Many person are not aware of the dangers of depression. It's hard to know the symptoms and overcome depression early on. In this case adolescents are the most vulnerable to the disease because at that time humans are in a transition phase from childhood to adulthood. WHO says every second there is a case of suicide due to severe depression. Based on these cases the researchers aimed to make an application to help the community, especially students, to be able to recognize and diagnose depression from an early age. The system in this application is an expert system using the Certainty Factor and Forward Chaining method. Inputs received by this application are biodata and psychological questions about the symptoms experienced by the user. The resulting output is the diagnosis, as well as the percentage of possible diseases suffered by user.
Keywords: Certainty Factor; Forward Chaining; Mental Illness; Expert System; Personality Test